Performance Analysis of Non-Renewable Energy in Bangladesh - M. G. Rabbani; C. T. Sattary; M. R. A. Mamun; M. M. Rahman; M. N. H. Khan (Institute of Advanced Engineering and Science, 2017)
The demand of energy is dramatically increased nowadays and the demand either can renewable or non renewable depends on the drawbacks. Hence, non renewable energies show the better performance where the limitations are comprisable very few and environmental friendly. Already developed countries are being used renewable energies as the main sources of energy to produce electricity where it proved the less easy and more benefits. However, non renewable energies such as natural gas, gas generator and so on still have been producing more and more electricity and this amount is around 10 times more than renewable energies especially developing countries like Bangladesh. This paper is being discussed the importance of renewable energies and non renewable energies to produce electricity, comparing the different countries electricity production and the using sources. Here analysis the data of different power plants in Bangladesh and the types of fuel, CO2 emission and electricity production. In additionally, Gazipur district has been selected to show the power consumption factories with the cost analysis in selected fuel types.